Introduction of Local Tourist Destinations through Virtual Reality to Increase Tourist Attractiveness in the Digital Era in Village Bulukumba District South Sulawesi Province - Wahyuddin; Nur, Syahban (CV. Literasi Indonesia, 2025)
The introduction of local tourist destinations through Virtual Reality (VR) technology is an innovative solution to increase tourism attractiveness in the village of Bulukumba Regency, South Sulawesi, in the digital era. The background of this research is based on the low level of digital literacy and technology utilization among the community and tourism actors, as well as the lack of promotion of potential tourist destinations. The purpose of this service is to realize the application of VR to introduce local tourism more interactively and provide solutions to challenges such as accessibility and limited promotion. The implementation method includes the identification of tourism potential, preparation of educational materials, training in VR content creation, and virtual tour simulations. This activity involves local communities, tourism actors, and local governments. The training includes making 360° videos, using VR devices, and digital marketing strategies. Interim results show the enthusiasm of participants in utilizing VR, although there are obstacles such as limited basic technological knowledge and the busyness of the community. This service concludes that VR technology has great potential to increase the promotion of Village tourism more attractively and sustainably. Continuous training support and collaboration with local communities are the keys to successful VR implementation. The outputs of this activity include publication articles, video documentation, and VR content of tourist destinations that can be used as effective promotional tools on digital platforms.